Indocyanine green labeling for optical and photoacoustic imaging of mesenchymal stem cells after in vivo transplantation. Issue 5 (1st February 2019) - Filippi, Miriam; Garello, Francesca; Pasquino, Chiara; Arena, Francesca; Giustetto, Pierangela; Antico, Federica; Terreno, Enzo
Abstract : The transplantation of mesenchymal stem cells (MSCs) holds great promise for the treatment of a plethora of human diseases, but new noninvasive procedures are needed to monitor the cell fate in vivo . Already largely used in medical diagnostics, the fluorescent dye indocyanine green (ICG) is an established dye to track limited numbers of cells by optical imaging (OI), but it can also be visualized by photoacoustic imaging (PAI), which provides a higher spatial resolution than pure near infrared fluorescence imaging (NIRF). Because of its successful use in clinical and preclinical examinations, we chose ICG as PAI cell labeling agent. Optimal incubation conditions were defined for an efficient and clinically translatable MSC labeling protocol, such that no cytotoxicity or alterations of the phenotypic profile were observed, and a consistent intracellular uptake of the molecule was achieved. Suspensions of ICG‐labeled cells were both optically and optoacoustically detected in vitro, revealing a certain variability in the photoacoustic spectra acquired by varying the excitation wavelength from 680 to 970 nm. Intramuscular engraftments of ICG‐labeled MSCs were clearly visualized by both PAI and NIRF over few days after transplantation in the hindlimb of healthy mice, suggesting that the proposed technique retains a considerable potential in the field of transplantation‐focused research and therapy. Stem cells were labeled with the Food and Drug Administration (FDA)‐approved fluorescent dye ICG, and detected by both PAI and OI, enabling to monitor the cell fate safely, in dual modality, and with good sensitivity and improved spatial resolution. Abstract : Photoacoustic imaging (PAI) is an emergent technique for cell imaging by means of nano‐sized contrast agents. Here, in vitro and in vivo PAI of stem cells is shown after labeling with the small molecule indocyanine green, an FDA‐approved fluorescent dye providing the in vivo cell fate surveillance with safety, improved spatial resolution, good sensitivity and the opportunity to integrate photoacoustic information with optical imaging.